THE EFFECT OF THREE DIMENSIONAL MEDIA TO INCREASE STUDENT LEARNING RESULT IN CUBE AND BEAM MATERIALS IN CLASS V SD STATE 21 MENDO WEST - Nurwindi Nurwindi; Aprian Giosaputra (Universitas Negeri Medan, 2019)
Abstract:The problem in this research study is the low of the result of class V student at SD Negeri 21 Mendo West and the absence of media used in the lesson of Mathematics. The purpose of this study is to Determine the influence of Three Dimensional Media to improve student learning outcomes on the material of cubes and blocks in Class V Elementary School 21 West Mendo. This research uses quantitative research with